Kontrowersje wokół analizy dyskursu - Heinemann, Wolfgang; Bilut-Homplewicz, Zofia; Smykała, Marta (Stylistyka, 2020)
The starting point o f this contribution is the assumption that there is an overall uncertainty about the use o f the term discourse in various disciplines. The author presents different ways of understanding discourse in philosophy (primarily by Habermas and Foucault). The core part of the paper discusses the heterogeneous linguistic concepts of discourse, starting from the idea o f discourse as a simple conversation through Critical Discourse Analysis and institutionalised interai rons up to textology-based concept of discourse. Particular attention is devoted to the use o f the notion o f discourse in sociology (and its related disciplines such as historiography, political science and media stuaies). When describing the concepts o f discourse in various disciplines the author draws attention to the vaned methods o f discourse analysis applied there, including the universal model by Wamke/Spitzmiiller. The finał section identifies and critically discusses problem areas in discourse studies. The paper also postulates that the current the fascination with Foucault should be abandoned wlien circumscribing the scope of discourse studies in favour of strwing for pragmatic and communicative adeąuacy.